444Frailty status and all-cause mortality in the community-dwelling individuals: An umbrella review. (2nd September 2021) - Ekram, A R M Saifuddin; Ryan, Joanne; Britt, Carlene; Espinoza, Sara; Woods, Robyn
Abstract: Background: Frailty is increasingly recognised for its association with adverse health outcomes, including mortality. However, various measures are used to assess frailty, and the strength of association could vary depending on the specific definition used. This umbrella review aims to map which frailty scale can best predict the relationship between frailty and all-cause mortality among community-dwelling older people. Methods: A protocol was registered at PROSPERO, and it was conducted following the PRISMA statement. MEDLINE, Embase, PubMed, Cochrane Database of Systematic Reviews, Joanna Briggs Institute (JBI) EBP database, and Web of Science database was searched. Methodological quality was assessed using the JBI critical appraisal checklist and online AMSTAR-2 critical appraisal checklist. For eligible studies, essential information was extracted and synthesized qualitatively. Results: Five systematic reviews were included, with a total of 434, 115 participants. Three systematic reviews focused on single frailty scales; one evaluated Fried's physical frailty phenotype and its modifications; another focused on the deficit accumulation frailty index. The third evaluated the FRAIL (Fatigue, Resistance, Ambulation, Illness, and Loss of weight) scale. The two other systematic reviews determined the association between frailty and mortality using different frailty scales. All of the systematic reviews found that frailty was significantly associated with all-cause mortality. Conclusion: This umbrella review demonstrates that frailty is a significant predictor of all-cause mortality, irrespective of the specific frailty scale. Key messages: Frailty is associated with an increased risk of all-cause mortality in community-dwelling individuals signifying the importance of assessment in the primary healthcare setting.